PENGARUH POLA ASUH ORANGTUA TERHADAP MOTIVASI BELAJAR SISWA: SEBUAH SYSTEMATIC LITERATURE REVIEW - Wiji Astuti, Wiwik; Nurveryani , Andi (Universitas Cokroaminoto Palopo, 2026)
This study is a Systematic Literature Review (SLR) aimed at examining empirical evidence related to the influence of parenting styles on student learning motivation at various levels of education. The study subjects included elementary, secondary, and higher education students in international research. The research method is a literature study by collecting relevant references from scientific articles, research reports and relevant journal publications. Data collection techniques included identifying relevant articles using specific keywords, assessing study quality, and thematic coding. Data analysis was conducted qualitatively using narrative synthesis of selected research findings. The review results indicate that parenting styles, particularly authoritative/authoritative and responsive parenting styles, are positively correlated with student learning motivation, while highly authoritarian or permissive styles can have a less than optimal impact on student motivation. The implications of this research are important for the development of family interventions and educational policies that support parental involvement in children's learning.